1994
DOI: 10.1017/s0272263100012870
|View full text |Cite
|
Sign up to set email alerts
|

Attention in Cognitive Science and Second Language Acquisition

Abstract: This paper examines how the cognitive notion of attention has been employed in SLA and how it is understood in cognitive science. It summarizes recent research on attention from cognitive and neuroscience approaches. Some reformulations of problems raised in SLA research related to attention are proposed. Current research offers detailed ideas about attention and its component processes. These ideas, elaborated theoretically and empirically in cognitive neuroscience, may help untangle some important but diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
394
0
14

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(419 citation statements)
references
References 52 publications
11
394
0
14
Order By: Relevance
“…In accordance with existing research, three separable but associated attentional sub-processes are assumed, that is, alertness, orientation, and detection (Schmidt 2001;Tomlin and Villa 1994). In this conceptualization of attention, alertness refers to an individual's general readiness to deal with incoming stimuli; orientation concerns the allocation of resources based on expectations about the particular class of incoming information; during detection, attention focuses on specific details.…”
Section: Construct Definitionsmentioning
confidence: 94%
“…In accordance with existing research, three separable but associated attentional sub-processes are assumed, that is, alertness, orientation, and detection (Schmidt 2001;Tomlin and Villa 1994). In this conceptualization of attention, alertness refers to an individual's general readiness to deal with incoming stimuli; orientation concerns the allocation of resources based on expectations about the particular class of incoming information; during detection, attention focuses on specific details.…”
Section: Construct Definitionsmentioning
confidence: 94%
“…According to Tomlin and Villa (1994), context facilitates second language acquisition when learners (1) discern elements of linguistic input from exposure; (2) perceive new or unusual characteristics in the event; and (3) establish a relationship between the linguistic input and the mental representation of the event. In this study, students reported that words were mostly noticed when they accompanied with the main characters' dramatic facial expressions and tones.…”
Section: Context Facilitates Learningmentioning
confidence: 99%
“…Pragmatic competence, for example, would require some awareness to be focused both on forms as such, and on their functional meanings in the social contexts in which they occur (Schmidt 1993). Tomlin & Villa (1994) disagree with Schmidt on the necessity of awareness for learning, and Al-Hejin (2004) also takes a more cautious stance, but concludes that both attention and awareness (and hence noticing) facilitate learning. This will be the assumption made in the rest of this paper.…”
Section: Consciousness/awarenessattention and Noticingmentioning
confidence: 99%